Students’ Perception on Borobudur Temple as Mathematic Learning Resource - Sri Wulandari Danoebroto (SEAMEO Regional Centre for QITEP in Mathematics, 2017)
This study aims to describe junior high school student’s perception of Borobudur Temple as mathematic learning resources. Borobudur Temple is well known as having extraordinary architecture built algorithmically. The parts of Borobudur Temple such as the stupa, statue, and wall carvings (relief) consist of many geometric models. This study employs an ethnomathematics perspective in describing perceptions about cultural artefacts as a mathematical model. The result of this study may be used as a basis for developing meaningful mathematic learning in schools. The sample of the study was 313 students ofjunior high school located near Borobudur Temple. The measure of the sampling adequacy with KMO is 0.86 from which confirms that the number of the sample is sufficient. The data were collected using a questionnaire with Likert scale 1 to 4 with the following range: (1) disagree, (2) neutral, (3) agree, and (4) strongly agree. The exploratory factor analysis yielded three factors of perception of Borobudur Temple as a mathematic model, those are: (1) Borobudur Temple is a geometry model, (2) Borobudur Temple can be used as mathematic learning source at school, and (3) learning mathematics from Borobudur Temple is helpful for students. The total variance reached 49,572%. The value of Cronbach alpha was 0,8204 for the 14 items. The data were analyzed using descriptive statistics to attain average items of mean and average standard deviation for each factor. The result of the research shows that: (1) students agree that Borobudur Temple is a geometry model, (2) Borobudur Temple can be used as mathematic learning source at school, and (3) learning mathematics from Borobudur Temple is helpful for them.